KEANEKARAGAMAN DAN ZONASI VEGETASI MANGROVE DI KAWASAN WISATA ALAM BANDAR BAKAU DUMAI SEBAGAI RANCANGAN MEDIA BOOKLET MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Qonita S, Sakinah; Nursal, Nursal; Fauziah, Yuslim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Research has been carried out to determine the types of mangrove plants and the zoning of mangrove vegetation in the Wisata Alam Bandar Bakau Dumai Area in October-December 2020. The results of the research on the diversity and zoning of mangrove vegetation in Bandar Bakau were integrated to design a media booklet on the concept of biodiversity related to the results of this study. The selection of locations was carried out using a purposive random sampling technique consisting of four stations. Each of the two transects with an observation plot of 20 x 20 meters. The parameters in this study are zoning based on the presence of mangroves, substrate texture and soil pH. The supporting parameters are the composition of the substrate fraction, salinity (water and substrate), pH (water and substrate) and DO. The results showed that the Wisata Alam Bandar Bakau Dumai Area contained 14 species, namely Avicennia alba, Avicennia lanata, Bruguiera sexangula, Bruguiera cylindrica, Bruguiera gymnorrhyza, Ceriops decandra, Heritiera littoralis, Lumnitzera littorea, Lumnitzera racemosa, Nypa fruticans, Rhizophora apiculata, Scyphiphora hydrophyllacea, Sonneratia alba, and Xylocarpus granatum. Zoning is formed based on the existence of open, middle, and land. The zoning formed based on the type of substrate consists of three, namely sand, loamy sand, and sandy clay. While the zoning formed based on the pH of the substrate is not visible because the pH value of 5-7 is spread throughout the station. The results of the study can be used as a booklet design for the material on Biodiversity Grade X High School.Key Words: Biodiversity, zone, Bandar Bakau Dumai, booklet